2018
DOI: 10.1192/bjp.2018.233
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation therapies for treatment-resistant depression: systematic review and meta-analysis

Abstract: BackgroundDepression is considered to have the highest disability burden of all conditions. Although treatment-resistant depression (TRD) is a key contributor to that burden, there is little understanding of the best treatment approaches for it and specifically the effectiveness of available augmentation approaches.AimsWe conducted a systematic review and meta-analysis to search and quantify the evidence of psychological and pharmacological augmentation interventions for TRD.MethodParticipants with TRD (define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 44 publications
(106 reference statements)
2
77
1
2
Order By: Relevance
“…Lithium and second/third generation antipsychotics remain preferred options for augmentation in treatment-resistant depression (Bassett et al, 2019; Mulder et al, 2018; Strawbridge et al, 2019).…”
Section: Response To Treatmentmentioning
confidence: 99%
“…Lithium and second/third generation antipsychotics remain preferred options for augmentation in treatment-resistant depression (Bassett et al, 2019; Mulder et al, 2018; Strawbridge et al, 2019).…”
Section: Response To Treatmentmentioning
confidence: 99%
“…A treatment strategy that our study did not explore was the use of pharmacological augmentation to antidepressants instead of augmentation with psychotherapy. However, there is no meta-analysis estimating the effect size of pharmacological augmentation vs. antidepressant only as first line treatment in MDD and in TRD the effect size of this treatment on symptom improvement is similar to that reported for augmentation with psychotherapy (Cuijpers et al, 2014;Ijaz et al, 2018;Zhou et al, 2015;Strawbridge et al, 2019). However, if a drug with very good tolerability profile is demonstrated to have similar or better efficacy than psychotherapy for augmenting treatment in MDD, combined treatment with this drug would be cost-effective compared to combined treatment with psychotherapy.…”
Section: Discussionmentioning
confidence: 85%
“…The direct evidence estimated a pooled ES = 0.29 (95% CI 0.21-0.37; p<0.001; I 2 = 99%) for antipsychotics vs placebo (13 studies), ES = 0.07 (95% CI −0.18-0.33; p<0.57; I 2 = 22%) for mood stabilisers vs placebo (3 studies), ES = 0.91 (95% CI 0.67-1.16; p<0.001; I 2 =77%) for N-methyl-D-aspartate (NMDA) antagonists vs placebo (5 studies). 28 The authors of this NMA suggested NMDA therapies as having the "highest chance of being an effective treatment 29 In this second meta-analysis, the ES across classes appears more similar with overlapping confidence intervals. Three lithium studies included in this second meta-analysis contributed to an estimated ES = 1.00 (95% CI 0.81-1.20; I 2 =0%).…”
Section: Choice Of Augmentation Strategymentioning
confidence: 81%
“…16,23,66,67,87 A recent systematic review and meta-analysis assessed the effectiveness, expressed as effect size (ES), of psychological and pharmacological augmentation interventions for TRD. 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation